1995
DOI: 10.1007/bf02208351
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in Saudi patients

Abstract: Eighty-seven patients with systemic lupus erythematosus (SLE) were retrospectively studied in King Khalid University Hospital, Riyadh. There were 78 females and 9 males (F:M ratio of 9:1). The mean age (+/- SD) at onset and at diagnosis were 25.3 +/- 10.5 and 28.5 +/- 10.9 years, respectively, with peak incidence in the 20-30 year age group. Musculoskeletal (91%), constitutional (76%), cutaneous (72%) and renal (63%) manifestations occurred most frequently, while neuropsychiatric manifestations (26%), photosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
35
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
13
35
4
Order By: Relevance
“…In our study, overall consanguinity rate between patients' parents was high in both familial and sporadic group (61.5% vs. 58.8%; Table 3). These results could suggest that consanguinity may be the cause of higher prevalence of SLE in Saudi Arabia compared with developed countries [3]. In one study from Kuwaiti population [14], which is also considered highly consanguineous, the prevalence of familial SLE was 27.4%, which is almost identical to our results (27.7%; Table 2).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, overall consanguinity rate between patients' parents was high in both familial and sporadic group (61.5% vs. 58.8%; Table 3). These results could suggest that consanguinity may be the cause of higher prevalence of SLE in Saudi Arabia compared with developed countries [3]. In one study from Kuwaiti population [14], which is also considered highly consanguineous, the prevalence of familial SLE was 27.4%, which is almost identical to our results (27.7%; Table 2).…”
Section: Discussionsupporting
confidence: 88%
“…A study conducted in Al-Qaseem region of Saudi Arabia showed prevalence of SLE of 19.28 per 100,000 people [2]. There were studies showing both higher [3] and lower [4] prevalence of SLE in Saudi Arabia compared to developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Such frequencies were noted in South African and Saudi patients. 12,27 The frequency of anticardiolipin antibodies and antib2 glycoprotein I brought up in our series is probably explained by the fact that they were sought especially in cases of obstetric or thrombotic manifestations of antiphospholipid syndrome.…”
Section: 17mentioning
confidence: 83%
“…It has been postulated that the disparate course and outcome observed among patients with SLE from different populations relates to the patients' biologic and immunogenetic 1,20 features and/ or to their socioeconomic status. [7][8][9][10][11][12][13][14] Some studies have reported the frequency of clinical features of SLE in Tunisia but are often not representative of the actual spectrum of SLE because the cohort originated from a definite geographical area and does not include patients from all parts of Tunisia.…”
Section: 17mentioning
confidence: 99%
See 1 more Smart Citation